Ambient effects on electrical characteristics of CVD-grown monolayer MoS2 field-effect transistors - Jae-Hyuk Ahn (Nature Portfolio, 2017)
Abstract Monolayer materials are sensitive to their environment because all of the atoms are at their surface. We investigate how exposure to the environment affects the electrical properties of CVD-grown monolayer MoS2 by monitoring electrical parameters of MoS2 field-effect transistors as their environment is changed from atmosphere to high vacuum. The mobility increases and contact resistance decreases simultaneously as either the pressure is reduced or the sample is annealed in vacuum. We see a previously unobserved, non-monotonic change in threshold voltage with decreasing pressure. This result could be explained by charge transfer on the MoS2 channel and Schottky contact formation due to adsorbates at the interface between the gold contacts and MoS2. Additionally, from our electrical measurements it is plausible to infer that at room temperature and pressure water and oxygen molecules adsorbed on the surface act as interface traps and scattering centers with a density of several 1012 cm−2 eV−1, degrading the electrical properties of monolayer MoS2.